Penerapan Metode Project Based Learning (PJBL) Sebagai Upaya Mengembangkan Kemampuan Berfikir Kritis Dan Kreatif Mahasiswa Prodi Psikologi Islam Pada Mata Kuliah Psikologi Umum Di UIT Lirboyo Kediri - Moch. Zidan Nur Adnan; A.M, Nila Ainu Ningrum; Moh. Irmawan Jauhari (PT. Hasba Edukasi Mandiri, 2025)
The project-based learning (PJBL) method is used in the learning process to enhance students’ critical and creative thinking skills. This research originated from the need to improve students’ abilities in facing the challenges of modern education, which require analytical capacity, problem-solving skills, and innovation. PJBL was selected because it emphasizes solving real-world projects and encourages students to collaborate and engage in investigative processes. A descriptive qualitative method was employed in this study, with data sources consisting of learning documents, course instructors, and students. Observation, interviews, and document analysis were used as data collection techniques. The results of the study indicate that the use of PJBL can increase student participation in learning activities, enhance their ability to analyze psychological concepts more deeply, and generate creative ideas in completing projects. This research is expected to serve as an innovative alternative learning method that can improve both the process and outcomes of learning in educational institutions.